2022
DOI: 10.1042/ebc20210100
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of plant innate immunity

Abstract: Transcriptional reprogramming is an integral part of plant immunity. Tight regulation of the immune transcriptome is essential for a proper response of plants to different types of pathogens. Consequently, transcriptional regulators are proven targets of pathogens to enhance their virulence. The plant immune transcriptome is regulated by many different, interconnected mechanisms that can determine the rate at which genes are transcribed. These include intracellular calcium signaling, modulation of the redox st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 130 publications
(142 reference statements)
0
9
0
Order By: Relevance
“…The WRKY family of transcription factors (TFs) is the major group of TFs in higher plant species [ 28 ]. Various studies have confirmed the significant biological role of WRKY TFs in plant growth, and biotic and abiotic stress responses as they are also actively involved in metabolism, including carbohydrate synthesis, aging, and the production of secondary metabolites, as well as in plant responses to pathogen infection [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The WRKY family of transcription factors (TFs) is the major group of TFs in higher plant species [ 28 ]. Various studies have confirmed the significant biological role of WRKY TFs in plant growth, and biotic and abiotic stress responses as they are also actively involved in metabolism, including carbohydrate synthesis, aging, and the production of secondary metabolites, as well as in plant responses to pathogen infection [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional reprogramming is an integral part of plant immunity 44 . To better understand the mechanism underlying the activation of the immune system in IL5-Ax, we screened the promoters of the 1,717 differentially expressed genes (DEGs; q < 0.001) between IL5-Ax and IL5-Ex for conserved cis -elements (Supplementary Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…These signaling cascades promote local physiological responses to impede invaders such as callose deposition, stomatal closure, and ethylene and SA biosynthesis. Ultimately, signaling leads to large-scale transcriptional reprogramming via activation of defense-related transcription factors (such as WRKY, bZIPs, and BHLHs) that promote the generation of antimicrobial components to fight pathogen attack [ 15 ]. The biosynthesis of the immune signal salicylic acid (SA) occurs in various subcellular compartments, including the cytosol and chloroplasts [ 16 ].…”
Section: Immunity and Light Signalsmentioning
confidence: 99%